Pragmatic deviation of politeness principle in Trump’s political speeches - Hamza, Muhammad Hussain; Nordin, Nur Rasyidah Mohd (Research Journal in Advanced Humanities, 2023)
The current study aimed to pragmatically explore the deviation from Leech's (2014) politeness maxims in the former president of the US Donald Trump's political speeches. A qualitative approach was followed to collect and analyze the data. Two oral documents; an interview and a speech that were taken from YouTube were adopted in this study as an instrumentation. These documents, which were selected purposively to saturate the data, were Trump's interview with Fox News Channel reporters, Martha MacCallum and Bret Baier in Scranton on March 6, 2020, and Trump's direct speech to the crowd in Illinois on June 25, 2022, in support of his candidates to win the Congressional election. A discourse analysis method was used to examine the data. The findings showed that Trump from the maxims to convince the people that his opponents are unacceptable, elect Trump's candidates, influence the crowd to change their views of the world, ruin his rivals' image, show his period as the US president incomparable and better than any US presidents, deny accountability, reject to release others from blame, influence the public that the election was stolen to invoke wrath among his supporters, express his hatred towards others, and vent his own feelings to make people sympathetic to him.